Safeguarding natural and cultural heritage: the experiences of Teluk Bahang Fishing Communities, Penang, Malaysia - Suriati Ghazali (Environmental Management Society, Malaysia, 2011)
Traditional fishing lifestyles are intimately connectedd with natural environmenatal and are based on the sustainable use of local ecosystems.However threats to natural environment by both natural disaster and modern development resulted in fluctuations in resources abundance, which poses a number of challenges to fishing communities. This articles explores the experiences of fishing communities in Teluk Bahang, Penang, Malaysia in safeguarding natural and cultural heritage of their village. Informal interviews were carried out on household member that engaged in heritage-related activities. While they continue traditional lifestyles many are forced to adapt to changes in natural environment.However, some of the villages manage to use natural environment in creatives ways, which enable them to promote the idea of love our natural environmen and cultural heritage.